Finger Painting Effectiveness to Improve Sitting Tolerance of Children with Autism - Irdamurni Irdamurni; Nurhastuti Nurhastuti; Farida Mayar; Ardisal Ardisal (Journal of ICSAR, 2021)
The common issue found in children with hyperactive autism is their excessive mobility, like running around and disturbing their peers in the classroom. As a consequence, they cannot sit still for two minutes. This research aims to examine whether finger painting activity can improve the sitting tolerance of children with hyperactive autism. This research used a single-subject research method. The subject selected for this research was a child with autism. Findings from the research showed that finger painting activity could improve children’s sitting tolerance from 2.5 minutes to 30 minutes. Therefore finger painting has effectively improved the sitting tolerance of children with autism.